Synthesis of Novel Thiazolyl Hydrazine Derivatives and Their Antifungal Activity - Jianjun Zhu; Yazhen Chen; Fen Su; Peiyi Wang (Journal of Chemistry)
A series of novel thiazolyl hydrazine derivatives 3a–3o were synthesized and evaluated for their in vitro antifungal activity against six phytopathogenic strains, namely, Botryosphaeria dothidea (B. d.), Gibberella sanbinetti (G. s.), Fusarium oxysporum (F. o.), Thanatephorus cucumeris (T. c.), Sclerotinia sclerotiorum (S. s.), and Verticillium dahliae (V. d.), by the classical mycelial growth rate method. Biological assessment results showed that most of these target compounds showed good antifungal activity toward tested strains. Especially, compound 3l showed excellent antifungal activities against B. d. and G. s. with relatively lower EC50 values of 0.59 and 0.69 µg/mL, respectively, which were extremely superior to those of commercial fungicides fluopyram, boscalid, and hymexazol and were comparable to those of carbendazim. Given the excellent bioactivity of designed compounds, this kind of thiazolyl hydrazine framework can provide a suitable point for exploring highly efficient antifungal agents.